Analisis Penerapan Model Pembelajaran Group Investigation Dan Pengaruhnya Terhadap Kemampuan Berpikir Kritis Siswa pada Materi Kimia Unsur di Kelas XII MIA SMAN 5 Kota Jambi - Meri Diana; Putri Fadillah (Journal Evaluation in Education (JEE), 2022)
Purpose of research: research on the application of the study model of the group investigation on chemical materials and its impact on the students' critical thinking ability are aimed at seeing how the model is performing on the critical thinking ability of the xii class student at sman 5 city jambi.Methodology: the study is a korelational descriptive study with mixed method mixed method mixed nowadays embedded. Samples were determined by an elementary sampling technique with an expert consideration. Research instruments form an observation sheet for the performance of the model group investigation and student critical thinking ability. The data analysis is performed to see how the gi model's performance of critical thinking capabilities is done with Pearson's bivariate and t-testing. Major findings: gi model performance is categorized well, reviewed by teachers and students at an average of 78.55% and 74.5%. The results of the similarity of the two average data of model accessibility by teachers and students gained thitung = 0.5015 and ttabel = 4.3. Research results prove that the performance of the study model of the group investigation is going well and there is an influence between the performance of the study model group investigation with the students' critical thinking ability on an xii chemical element at the five cities jambi.Research update: this study strengthens a significant impact between gi models on students' critical thinking ability, especially at chemistry lessons.